2019
DOI: 10.3390/app9091956
|View full text |Cite
|
Sign up to set email alerts
|

Regularized Urdu Speech Recognition with Semi-Supervised Deep Learning

Abstract: Automatic Speech Recognition, (ASR) has achieved the best results for English, with end-to-end neural network based supervised models. These supervised models need huge amounts of labeled speech data for good generalization, which can be quite a challenge to obtain for low-resource languages like Urdu. Most models proposed for Urdu ASR are based on Hidden Markov Models (HMMs). This paper proposes an end-to-end neural network model, for Urdu ASR, regularized with dropout, ensemble averaging and Maxout units. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…Currently, the web repository contains 3D CT images of 10 confirmed COVID-19 cases shared for scientific purposes. The British Society of Thoracic Imaging (BSTI) in collaboration with Cimar UK's Imaging Cloud Technology deployed a free to use encrypted and anonymised online portal to upload and download medical images related to COVID-19 positive and suspected patients 9 . The uploaded images are sent to a group of BSTI experts for diagnosis.…”
Section: Online Data Setsmentioning
confidence: 99%
“…Currently, the web repository contains 3D CT images of 10 confirmed COVID-19 cases shared for scientific purposes. The British Society of Thoracic Imaging (BSTI) in collaboration with Cimar UK's Imaging Cloud Technology deployed a free to use encrypted and anonymised online portal to upload and download medical images related to COVID-19 positive and suspected patients 9 . The uploaded images are sent to a group of BSTI experts for diagnosis.…”
Section: Online Data Setsmentioning
confidence: 99%
“…The SIRM is hosting radiographical images of COVID-19 cases. 9 Their data set has been utilized by some of the cited works in this article. Another open source repository for COVID-19 radiographic images is Radiopaedia.…”
Section: Online Data Setsmentioning
confidence: 99%
“…Artificial Intelligence (AI) and Machine Learning (ML) techniques have been prominently used to efficiently solve various computer science problems ranging from bio-informatics to image processing. ML is based on the premise that an intelligent machine should be able to learn and adapt from its environment based on its experiences without explicit programming [8,9]. ML models and algorithms have been standardized across multiple programming languages such as, Python and R. The main challenge to the application of ML models is the availability of the open source data [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the designed supervised ML solution indicated that the decision forest model has the best performance for the prediction of structural type; therefore, the decision forest model was selected. Finally, a self-training process [30][31][32] was performed iteratively until the prediction accuracy was accepted. Specifically, the ML model was trained by the sample data, and then the prediction of the trained model was scored and evaluated, separately.…”
Section: Semi-supervised ML Solutionmentioning
confidence: 99%
“…training process [30][31][32] was performed iteratively until the prediction accuracy was accepted. Specifically, the ML model was trained by the sample data, and then the prediction of the trained model was scored and evaluated, separately.…”
Section: Semi-supervised ML Solutionmentioning
confidence: 99%